Determination of ethanamizuril, a novel triazine coccidiostat, in rat plasma by ultra‐performance liquid chromatography system‐tandem mass spectrometry and its application in a toxicological study. (20th August 2019) - Wang, Xiaoyang; Zhao, Juan; Wei, Shuya; Wang, Chunmei; Zhang, Lifang; Wang, Mi; Liu, Yingchun; Fei, Chenzhong; Xue, Feiqun; Zhang, Keyu
Abstract: Ethanamizuril is a new triazine compound that has the potential to be a novel anticoccidial drug. Toxicological studies in experimental rats were performed to understand the safety profile of ethanamizuril for drug product development. In this study, a novel, selective and accurate ultra‐performance liquid chromatography tandem mass spectrometry method has been developed for the determination of ethanamizuril concentrations in rat plasma. With 4‐nitro‐ o ‐cresol as an internal standard, sample pretreatment involved a one‐step extraction with acetonitrile of 100 μL plasma. The detection was carried out by electrospray ionization mass spectrometry in negative ion mode with selected ion recording. The standard curves were linear ( r 2  ≥ 0.999) over the concentration range of 0.1–100 μg/mL. The relative standard deviations of intra‐ and inter‐day precisions were less than 8.4 and 8.87%, respectively. The mean extraction recovery of ethanamizuril from rat plasma was 97.68–102.57%. The method was fully validated and successfully applied to monitor plasma concentrations of ethanamizuril in a short‐term toxicity study and two‐generation reproduction toxicity study. The result of the study confirmed that the elimination of ethanamizuril in rats is slow.